An Integrated Methodology for Supplier Selection under the Presence of Vagueness: A Case in Banking Sector, Turkey - Semih Onut; Suleyman Tosun (Journal of Applied Mathematics)
A supplier selection process mainly involves evaluation of different alternative suppliers based on different criteria. This process can be handled as a combination of the customer needs and the technical requirements. Also customers can be considered as the companies to purchase the suppliers’ technical expertise. Hence, this kind of relationship can be analyzed as a house of quality model typical of quality function deployment (QFD). This paper develops a supplier evaluation approach based on the analytic network process (ANP), QFD, and the technique for order performance by similarity to ideal solution (TOPSIS) methods to help an investment bank in Turkey as a real world application. Fuzzy logic is used to capture the vagueness in people’s verbal assessments. In the first phase, matrices used to define the importance of the supplier selection criteria and the technical requirements are calculated with the fuzzy ANP method. The technical requirements and the criteria are combined in the house of quality to evaluate the relationship between them. In the second phase, fuzzy TOPSIS is used to rank the suppliers based on the weighted criteria obtained from the first phase. The study was followed by the sensitivity analysis of the results.